The concept of fraction of drug transported (ft) with special emphasis on BBB efflux of CNS and antiretroviral drugs. Issue 4 (13th February 2015) - Prasad, B; Unadkat, JD
Abstract : The fraction of drug transported (ft ) into or out of a tissue is a concept useful to understand the impact of transporters on absorption, distribution, metabolism, and excretion (ADME) and tissue distribution of a drug. Here, ft is utilized to explain the impact of transporters on central nervous system (CNS) distribution of drugs, drug interactions (DDI), and to predict the unbound brain concentration (Cu, b ) of the drug. The latter is important to ascertain if Cu, b is sufficient for efficacy.